Evidence of effectiveness of a fracture liaison service to reduce the re-fracture rate. Issue 3 (March 2016) - Nakayama, A.; Major, G.; Holliday, E.; Attia, J.; Bogduk, N.
Abstract Summary We assessed the ability of a fracture liaison service (FLS) to directly reduce re-fracture risk. Having a FLS is associated with a ∼40 % reduction in the 3-year risk of major bone and ∼30 % of any bone re-fracture. The number needed to treat to prevent a re-fracture is 20. Introduction FLS have been promoted as the most effective interventions for secondary fracture prevention, and while there is evidence of increased rate of investigation and treatment at institutions with a FLS, only a few studies have considered fracture outcomes directly. We therefore sought to evaluate the ability of our FLS to reduce re-fracture risk. Methods Historical cohort study of all patients ≥50 years presenting over a 6-month period with a minimal trauma fracture (MTF) to the emergency departments of a tertiary hospital with a FLS, and one without a FLS. Baseline characteristics, mortality and MTFs over a 3-year follow-up were recorded. Results Five hundred fifteen patients at the FLS hospital and 416 patients at the non-FLS hospital were studied. Over 3 years, 63/515 (12 %) patients at the FLS hospital and 70/416 (17 %) at the non-FLS hospital had a MTF. All patients were analysed in an intention-to-treat analysis regardless of whether they were seen in the FLS follow-up clinic. Statistical analysis using Cox proportional hazard models in the presence of a competing risk of death from any cause was used. After adjustment for baseline characteristics, there was a ∼30 % reduction in rate of any re-fracture at the FLS hospital (hazard ratio (HR) 0.67, confidence interval (CI) 0.47-0.95, p value 0.025) and a ∼40 % reduction in major re-fractures (hip, spine, femur, pelvis or humerus) (HR 0.59, CI 0.39-0.90, p value 0.013). Conclusions We found a ∼30 % reduction in any re-fractures and a ∼40 % reduction in major re-fractures at the FLS hospital compared with a similar non-FLS hospital. The number of patients needed to treat to prevent one new fracture over 3 years is 20.